The Effect of Covid-19 Pandemic on the Maritime Industry and the Role of the Ship Registries - Panagiotis Saviolakis; Michalis Pazarzis (Emerging Science Journal, 2021)
Objectives: The current paper focuses on the impact of the unexpected event of the Covid-19 pandemic on the maritime industry. It searches the role adopted by key stakeholders of the shipping community with particular emphasis on the Ship Registries. Methods/Analysis: In order to conduct the research, there has been a thorough investigation concerning the initiatives taken by both governmental and private sector entities. Regulations and announcements issued to handle the Covid-19 pandemic are analysed and properly assessed. Findings: The response of the shipping sector, including the Ship Registries, was decisive and covered numerous aspects of maritime activity. Some of these actions taken can only be regarded as a temporary reply of the maritime industry to the threats imposed by the disease. At the same time, a significant part of these initiatives have a more permanent character and their acceptance by the maritime industry underlines their future potential. In this case, the appearance of the random event of the Covid-19 disease acted as a catalyst for developments in the shipping sector. Novelty/Improvement:This study is expected to contribute to the scientific orientation concerning the reaction towards the impact of future unexpected events with particular emphasis on the role of the Ship Registries. Doi: 10.28991/esj-2021-SPER-06 Full Text: PDF